2003
DOI: 10.1051/lait:2003014
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectroscopy: A tool for the investigation of cheese melting - Correlation with rheological characteristics

Abstract: -Trends in the texture and structure as a function of temperature were determined for 2 hard cheeses (Comté and Emmental) and 1 semi-hard cheese (Raclette) using dynamic testing rheology and front-face fluorescence spectroscopy. The storage modulus (G'), the loss modulus (G'') and the complex viscosity (h*) decreased while strain and tan d increased as the temperature increased from 5 °C to 60 °C. Protein tryptophan emission spectra and vitamin A excitation spectra were recorded on cheese samples at 5,10,15,20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 25 publications
4
40
0
1
Order By: Relevance
“…The shape of the spectra changes with the manufacturing process of the investigated cheeses. Recently, it has been reported that the shape of the vitamin A excitation spectrum is correlated with the physical state of the triglycerides in the fat globules [14,22,23]. Considering the short distance between tryptophan residues and vitamin A in the cheese matrix, fluorescence transfer between a donor (tryptophan) and an acceptor may be observed.…”
Section: Fluorescence Spectra Of Different Cheese Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape of the spectra changes with the manufacturing process of the investigated cheeses. Recently, it has been reported that the shape of the vitamin A excitation spectrum is correlated with the physical state of the triglycerides in the fat globules [14,22,23]. Considering the short distance between tryptophan residues and vitamin A in the cheese matrix, fluorescence transfer between a donor (tryptophan) and an acceptor may be observed.…”
Section: Fluorescence Spectra Of Different Cheese Varietiesmentioning
confidence: 99%
“…Indeed, much less information is available about the relation between the shape of the vitamin A spectra and the organisation of lipids than the shape of the tryptophan spectra and the protein structure. However, it is well known that the fluorescent properties of this fluorophore are very sensitive to changes in the solvent viscosity [19,22,23]. Recently, a good correlation between the shapes of the vitamin A fluorescence spectra and the viscosity of lipids in the fat globules have been found [14].…”
Section: Partial Least Squares Analysismentioning
confidence: 99%
“…Small-amplitude oscillatory shear or compression measurements were successfully used to study the viscoelastic behavior of food (Bertola et al 1992;Bowland and Foegeding 2001;Campanella et al 1987;Rosenberg et al 1995) and cheeses (Karoui et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…2b). The fluorescence intensity ratio F 320 /F 295 attributed to the physical state of the triglycerides of milk fat (Dufour et al 2000;Karoui et al 2003) increased from the young to ripened cheeses and shifted towards higher wavelengths with ripening. Hence, the excitation spectra of vitamin A characterize the physical state (viscosity) of the triglycerides in the milk fat and fat yield in the cheeses in the course of cheese ripening.…”
Section: Spectral Characteristicsmentioning
confidence: 99%